Deoxynivalenol: A Major Player in the Multifaceted Response of Fusarium to Its Environment - Kris Audenaert (Toxins, 2013)
The mycotoxin deoxynivalenol (DON), produced by several Fusarium spp., acts as a virulence factor and is essential for symptom development after initial wheat infection. Accumulating evidence shows that the production of this secondary metabolite can be triggered by diverse environmental and cellular signals, implying that it might have additional roles during the life cycle of the fungus. Here, we review data that position DON in the saprophytic fitness of Fusarium, in defense and in the primary C and N metabolism of the plant and the fungus. We combine the available information in speculative models on the role of DON throughout the interaction with the host, providing working hypotheses that await experimental validation. We also highlight the possible impact of control measures in the field on DON production and summarize the influence of abiotic factors during processing and storage of food and feed matrices. Altogether, we can conclude that DON is a very important compound for Fusarium to cope with a changing environment and to assure its growth, survival, and production of toxic metabolites in diverse situations.